Development Of A Pop-Up Book On The Basics Of Pendet Dance For Elementary Schools (Phase A) - Ni Luh N. Jeylita Paramacitha; Warih Handayaningrum (Journal of Pedagogi, 2024)
Pendet dance is a Balinese dance that contains a variety of basic movements including agem, tandang, tangkis, and tangkep. These movements are introduced early on or at the phase A elementary school level. To develop cognitive understanding, pop up books are used as learning media for the introduction of Pendet dance movements. Because this kind of media has never been available before, it is considered important to provide in schools. Therefore, it is necessary to have interesting learning media applied at SD Negeri Lidah Wetan II Surabaya. The purpose of this study is to describe, 1) the process of developing pop up book of Pendet dance basics as a form of art appreciation education for elementary school (phase A), 2) the feasibility of content components and appearance components of pop up book developed to produce quality books, and 3) user responses about pop up book of Pendet dance basics. Supported by the development method, the pop up book development process uses the Analyze, Design, Development, Implement, Evaluate stages. Validation by media and material experts showed that the content components and appearance of the pop up book were considered very feasible. User trials were conducted to determine student and teacher responses to the pop up book. The percentage of results shows that the pop up book gets a value from media validation of 82.5%, material validation of 92.5%, the first teacher's response of 90%, the second teacher's response of 95% and student responses that show an increase in the answer "yes" from each question asked. Thus, pop up book media can be used as a medium for introducing movement variety for elementary school (phase A) and students interact actively during the learning process through pop up book.